Efek Hipokolesterolemik Susu Kedelai Fermentasi Steril secara In Vitro - Fatma Zuhrotun Nisa’, Y.Marsono, Eni Harmayani (Berita Kedokteran Masyarakat (BKM), 2007)
Background: High blood cholesterol level is a risk factor of atherosclerosis, a condition causing coronary heart disease, obesity and others. The utilization of live cell like probiotic was proven to reduce cholesterol level in blood. The problem of the utilization of live cell was the low of distribution and difficulty in storage. Should be invented an alternate to produce the product with the same characteristic, that is, by utilization of inactive cell.Objective: to evaluate the effect of sterilized fermented soymilk on cholesterol reduction in vitro, that is the binding of cholesterol by the component of   sterilized fermented soymilk.Method: The ability of sterilized fermented soymilk to bind cholesterol was assayed using inoculation of sterilized fermented soymilk in MRS medium with 0,1% pure cholesterol then was incubated at 37 C for 24 hours. After incubation, the cholesterol level bonded was measured by O-Pthalaldehid method.Result: The research has shown that the sterilized fermented soymilk and the fermented milk could bind the cholesterol. The sterilized fermented soymilk could bind the cholesterol the higher than the non sterilized fermented soymilk.Conclusion: The sterilized fermented soymilk had the ability of cholesterol bindingKeywords: hypocholesterolemic, fermented soymilk